2008
DOI: 10.1590/s0004-282x2008000200004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with narcolepsy: a WHOQOL-bref study

Abstract: -Objective: To evaluate the perception of Quality of Life (QL) in Brazilian patients with narcolepsy. Method: 40 adult patients aged between 20 and 72 years (mean=41.55; SD=14.50); (28 F; 12M), with the diagnosis of chronic narcolepsy were followed up at the outpatient clinic (Patient Group). The Control Group was composed of 40 adults. The instrument utilized was the World Health Organization Quality of Life (WHOQOL-BREF). Results: The two groups were homogeneous and no difference was found with regards to ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…24 Consequently, these individuals show lower employment rates and income levels than healthy patients. 43 Narcolepsy is also associated with poor quality of life 44 and psychiatric disorders. 45 In a case-control study, Droogleever et al 46 found that 53% of narcoleptic patients report anxiety or panic attacks, which were mainly related to frightening episodes during hypnagogic hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…24 Consequently, these individuals show lower employment rates and income levels than healthy patients. 43 Narcolepsy is also associated with poor quality of life 44 and psychiatric disorders. 45 In a case-control study, Droogleever et al 46 found that 53% of narcoleptic patients report anxiety or panic attacks, which were mainly related to frightening episodes during hypnagogic hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a total of 21 studies met the inclusion criteria ( Table 2). 14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] …”
Section: Literature Search Methodologymentioning
confidence: 99%
“…ing sleep. The database characterizing such sleep patterns is limited but consistent, with patients reporting frequent awakenings after sleep onset and poor sleep quality, 22,31,[33][34][35]38 although only 3 studies provided a quantitative comparison of nocturnal awakenings (Table 3).…”
Section: Nighttime Sleep In Narcolepsymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Numerous studies have found health-related quality of life (HRQoL) among narcolepsy patients to be significantly impaired in comparison with healthy controls or the general population. [5][6][7][8][9][10][11][12][13][14] Patients are impaired on several domains of HRQoL including mood, psychopathology, and other areas such as marital and work problems. [5][6][7][8][9][10][11][12][13][14] Narcolepsy has been associated with a negative impact on work productivity including increased unemployment, 15 early retirement, 16 accidents at work, 5 welfare enrollment, 11 time missed from work, general impairment at work, 8 and lower wages.…”
Section: Introductionmentioning
confidence: 99%